2017
DOI: 10.1038/s41598-017-03550-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic capability of Pulsar perimetry in pre-perimetric and early glaucoma

Abstract: This study aimed to compare the diagnostic capability of Pulsar perimetry (Pulsar) in pre-perimetric glaucoma (PPG) and early glaucoma (EG) with that of Flicker perimetry (Flicker) and spectral-domain optical conference tomography (SD-OCT). This prospective cross-sectional study included 25 eyes of 25 PPG patients, 35 eyes of 35 EG patients, and 42 eyes of 42 healthy participants. The diagnostic capability using the area under the curve (AUC) of the best parameter and agreement of detectability between structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Understanding the relationship of visual field defects with RNFL or GCC thinning and vessel density reduction helps the clinicians develop strategies to detect glaucoma in the earliest stages. Hirasawa et al reported that the agreement between structural and specific functional measurements in patients with PPG and early glaucoma was poor; however, both groups were able to be diagnosed with 100% sensitivity using either structural or specific functional measurements [18]. We revealed that PP was more significantly correlated with vessel density of RPC and macula than SAP in pre-perimetric glaucoma eyes (Table 5), with high sensitivity at the best cut-off value in both PPG and PG groups (Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the relationship of visual field defects with RNFL or GCC thinning and vessel density reduction helps the clinicians develop strategies to detect glaucoma in the earliest stages. Hirasawa et al reported that the agreement between structural and specific functional measurements in patients with PPG and early glaucoma was poor; however, both groups were able to be diagnosed with 100% sensitivity using either structural or specific functional measurements [18]. We revealed that PP was more significantly correlated with vessel density of RPC and macula than SAP in pre-perimetric glaucoma eyes (Table 5), with high sensitivity at the best cut-off value in both PPG and PG groups (Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Its detectability of early glaucomatous visual field damage has been reported to be slightly inferior to that of the structural measurements by optical coherence tomography (OCT) [11,12]. On the other hand, functional measurements from non-conventional perimetry, such as Pulsar perimetry (PP), can assist to diagnose early glaucoma [13][14][15][16][17][18]. PP was initially reported by González-Hernandez et al in the 2000s [13,[19][20][21]; it can detect temporal and spatial contrast sensitivity functions simultaneously [15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Pomorska et al, 25 who compared the Stratus OCT results in 27 eyes with OH, 33 eyes with PPG (defined as the presence of any sign of glaucomatous optic neuropathy in the ophthalmoscopy examination) with 58 normal cases (control group), found AUCs ranging from 0.55 to 0.75 when comparing OH and controls and AUCs ranging from 0.75 to 0.89 when comparing PPG and controls. Hirasawa et al, 26 using the 3D OCT-2000 (Topcon, Tokyo, Japan), who compared 25 PPG cases with 43 normal cases (control group), obtained the best AUCs for the inferior quadrant RNFL thickness (AUC, 0.907) and for the inferior macular RNFL thickness (AUC, 0.861). However, in the current study, all cases are within grade 0 of the GSS with OH but without VF characteristics of grade I of the GGS, and this probably justifies the slightly lower values of AUC areas because it is more difficult to identify very early glaucomatous damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the current study, all cases are within grade 0 of the GSS with OH but without VF characteristics of grade I of the GGS, and this probably justifies the slightly lower values of AUC areas because it is more difficult to identify very early glaucomatous damage. These studies 25 , 26 also compared normal cases and PPG cases defined as having structural glaucomatous changes seen by ophthalmoscopy, such as rim thinning, notching, and RNFL thinning or defects. Therefore, it is logical to consider that the diagnostic ability of our GDC is lower because they have to detect cases with RNFL loss and those that do not present RNFL loss among cases in group 0 of the GSS and do not use any changes seen on ophthalmoscopy in the optic disc.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of circumpapillary retinal nerve fibre layer (cpRNFL) or macular ganglion cell layer (mGCL) tissue thickness by optical coherence tomography (OCT) and specific perimetry measurements, including frequency doubling technology (FDT), short wavelength automated perimetry (SWAP), Flicker perimetry and Pulsar perimetry, have been considered indices of the structural and functional changes in early glaucoma. [1][2][3][4][5] The process from the onset of glaucoma to the occurrence of structural and functional changes is expressed as the so-called glaucomatous continuum, and it has been proposed that changes in the glaucomatous continuum occur initially in the structure before function. 6 However, in the clinical setting, some patients have evidence of glaucomatous optic neuropathy without a detectable visual field abnormality, and others have a glaucomatous visual field without detectable structural abnormality.…”
Section: Introductionmentioning
confidence: 99%